Higher Urinary Dopamine Concentration is Associated with Greater Ad Libitum Energy Intake in Humans. Issue 5 (14th April 2020) - Basolo, Alessio; Ando, Takafumi; Hollstein, Tim; Votruba, Susanne B.; Krakoff, Jonathan; Piaggi, Paolo
Abstract : Objective: This study aimed to assess the relationship between dopamine, a neurotransmitter involved in feeding behavior, and ad libitum energy intake in humans. Methods: Healthy individuals ( n  = 158; 72 Native American, 50 white, 18 black, and 18 Hispanic participants; BMI: 33 [SD 9] kg/m 2 ; body fat: 33% [SD 9%]) were admitted for two inpatient studies investigating the determinants of ad libitum energy intake and assessed for 3 days using a highly reproducible, computerized vending machine paradigm. Urine was collected for 24 hours during eucaloric conditions prior to the ad libitum feeding period, and urinary dopamine excretion rate was quantified by high‐performance liquid chromatography. Results: Urinary dopamine excretion rate was on average 346 ± 106 μg over 24 hours and was positively correlated with BMI ( r  = 0.28, P  < 0.0001). Higher dopamine concentrations were associated with lower cognitive restraint (ρ = −0.25, P  = 0.005) and greater total ad libitum energy intake ( r  = 0.29, P  = 0.0002). However, after adjustment for anthropometrics, in black and white cohorts, higher dopamine concentrations were associated with greater total ad libitum energy intake ( r  = 0.70, P  = 0.001 and r  = 0.33, P  = 0.02, respectively), whereas no associations were observed in Native American or Hispanic cohorts (all P  > 0.3). Conclusions: Higher urinary dopamine concentrations are associated with greater ad libitum energy intake, indicating a role for dopamine in the reward pathway regulating human feeding behavior.